NATIONAL SPIRITUALITY AND MUSIC - A. Nurmuhamedjanov (Innovate Conferences, 2025)
This article examines musical spirituality as an inseparable component of the nation’s spiritual life. It discusses the views of major thinkers on the place and significance of music in human existence and highlights the role of social-philosophical research in educating youth in the spirit of national values while advancing science, spirituality, and musical thinking. Particular attention is given to the historical continuity of musical practice, its therapeutic and ethical dimensions, and its relevance to the cultural vision often referred to as the “New Uzbekistan.”
Keywords: spirituality, music, feeling, maqom (classical modal tradition), love and affection, human emotions, objective reality, upbringing, “wordless philosophy.”